Opposite correlation of 25-hydroxy-vitamin D- and 1,25-dihydroxy-vitamin D-metabolites with gestational age, bone- and lipid-biomarkers in pregnant women - Oleg Tsuprykov (Nature Portfolio, 2021)
Abstract 25-Hydroxyvitamin D (25OHD) and 1,25-dihydroxyvitamin D (1,25(OH)2D) need to be bound to carrier proteins to be transported to their target cells. The majority of either 25OHD or 1,25(OH)2D is bound to vitamin D-binding protein (DBP), a smaller fraction is bound to albumin and only very small amounts of 25OHD or 1,25(OH)2D are free. Albumin-bound 25OHD or 1,25(OH)2D is relatively easily available after dissociation from albumin. Thus, the sum of free and albumin-bound forms is called bioavailable 25OHD and bioavailable 1,25(OH)2D. Total 25OHD and 1,25(OH)2D are defined as the sum of free, albumin-bound and DBP-bound 25OHD and 1,25(OH)2D, respectively. This cross-sectional study in 427 pregnant women compared the correlation of the six vitamin D compounds with biomarkers of bone health, lipid metabolism, kidney function, endocrine parameters, and group B water-soluble vitamins. Among the 25OHD metabolites analysed, total 1,25(OH)2D showed clearly the best correlation with calcium, bone-specific alkaline phosphatase, adiponectin, LDL, HDL, urea, thyroxine, and group B water-soluble vitamins. When comparing the three 25OHD metabolites, both free 25OHD and bioavailable 25OHD showed overall good correlations with calcium, bone-specific alkaline phosphatase, adiponectin, LDL, HDL, urea, thyroxine, triiodothyronine, and group B water-soluble vitamins, The correlations of 1,25(OH)2D and 25OHD metabolites went always in opposite directions. Only PTH correlates always inversely with all six vitamin D compounds. In conclusion, free 25(OH)D and bioavailable 25(OH)D are more precise determinants of the vitamin D status than total 25(OH)D in normal pregnancy, whereas total 1,25(OH)2D is superior to free and bioavailable 1,25(OH)2D. Except for PTH, correlations of 25(OH)D and 1,25(OH)2D metabolites with typical clinical chemistry readouts go in opposite directions.